Ovarian granulosa cell tumor and increased risk of breast cancer. (28th October 2013) - Hammer, Anne; Lauszus, Finn F.; Petersen, Astrid C.
Abstract Granulosa cell tumor of the ovary (GCT) is a rare neoplasm. The tumor often secretes estrogens and then presents at an earlier stage due to hormone‐related symptoms. GCT women are at increased risk of endometrial carcinoma, but there is only limited information about GCTs and potential association to other hormone‐related neoplasms such as breast cancer. We conducted a retrospective follow‐up study on 163 women with GCT. Medical records and histological sections were reviewed and a search in the pathology registry performed. Eight [95% confidence interval (CI); 3.4–15.8] GCT women were diagnosed with a breast neoplasm; one with Paget's disease of the nipple and seven with breast carcinoma. Based on calculations using incidence rates on breast cancer among Danish women, we would have expected 2.5 cases of breast cancer. The odds ratio was 3.3 (95% CI, 1.6–6.6), suggesting an increased risk of breast cancer in GCT women.